State of Food (in)Security in Chepang Community: A Case of Dahakhani VDC, Chitwan - Aryal, Badri (Economic Literature, 2016)
This study intends to investigate food (in) security situation of Chepang communities as well as their food coping strategies based on 48 sample households in Dahakhani Village Development Committee, Chitwan. On an average they possess low level of assets and meager amount of crops and animal husbandry products. Consequently, most of the Chepang are found food insecure. Social services like school and drinking water sources are supplied within half an hour walking distance from their home whereas institutions are 3 hours far from home. Correlation analysis showed highly significant relationship between number of food insufficient months and number of livestock and birds in the household; between number livestock and birds with quantities of cereal production in a year. There is significant association of quantity of cereal production and land holding size with number of food insufficient months for a year. It can be inferred that meat is one of the important component of Chepang food habit and promotion of livestock rising can be an important supplement to Chepang diets. Economic Literature, Vol. XI (60-66), June 2013